Tidal Flood Susceptibility Mapping and Community Adaptation Assesment in Semarang Utara District - Jabbar, Abdul; Fariz, Trida Ridho; Putri, Salma Dwi; Rahmawati, Dwi; Prahmani, Yonika Sindiana; Putri, Rizda Amalia; Siregar, Zepanya Gladis Tabita; Holeng, Vera Angelina; Chasanah, Aisya Nurul (Journal of Environmental and Science Education, 2023)
North Semarang District is one of the areas that is often affected by tidal floods. This study will discuss flood distribution through tidal flood susceptibility mapping and identify adaptations. The first step is to carry out flood susceptibility mapping using DEMNAS data and sea tides. The second stage is to determine the key areas based on the tidal flood susceptibility map made. Key areas are useful for identifying forms of community adaptation to tidal floods through data collection in the form of observations and interviews. The mapping results show that the flood susceptibility area reaches 582.89 Ha or around 50% of the area of North Semarang District. The key areas with high susceptibility are settlements on Jalan Tambakrejo, Tanjungmas Village and it is known that the community responds by adapting patterns to changes in physical infrastructure, economic activity, and social development.